Lactic acid derivatives with terphenyl molecular core. Issue 9 (14th July 2016) - Novotná, Vladimíra; Hamplová, Věra; Sasnouski, Genadz; Salamon, Peter
ABSTRACT: New lactic acid derivatives, based on terphenyl molecular core laterally substituted by chlorine atom, have been synthesised and their liquid crystalline properties studied. We varied the molecular structure by prolonging the non-chiral chain and analysed the mesogenic properties with respect to its length. We found that all new compounds reveal the SmA*–SmC* phase sequence in an extremely broad temperature interval. The experimental techniques, namely the polarising optical microscopy, differential scanning calorimetry, x-ray diffraction and helical pitch measurements, have been applied to establish the physical properties. Studied compounds exhibit very high values of the spontaneous polarisation and the tilt angle grows continuously on cooling up to 42°. The pitch values drop down when prolonging the molecular non-chiral chain. GRAPHICAL ABSTRACT: